2021
DOI: 10.1371/journal.pone.0248957
|View full text |Cite
|
Sign up to set email alerts
|

The characteristics and evolution of pulmonary fibrosis in COVID-19 patients as assessed by AI-assisted chest HRCT

Abstract: The characteristics and evolution of pulmonary fibrosis in patients with coronavirus disease 2019 (COVID-19) have not been adequately studied. AI-assisted chest high-resolution computed tomography (HRCT) was used to investigate the proportion of COVID-19 patients with pulmonary fibrosis, the relationship between the degree of fibrosis and the clinical classification of COVID-19, the characteristics of and risk factors for pulmonary fibrosis, and the evolution of pulmonary fibrosis after discharge. The incidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
105
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(125 citation statements)
references
References 22 publications
4
105
0
1
Order By: Relevance
“…Pulmonary function testing in these subjects revealed a correlation between reduced DLCO and severity of illness with women and elderly patients having a higher likelihood of having a diffusion impairment. Other studies have found that higher inflammatory markers (C-reactive protein, LDH and interleukin-6) ( 102 , 110 – 112 ), high d-dimer ( 113 ), white blood cell count ( 110 ), albumin level ( 102 ), older age ( 74 , 113 ), male sex ( 113 , 114 ), underlying co-morbidities ( 113 ), ICU admission ( 114 ), longer hospital stay ( 74 , 111 ), the need for mechanical ventilation ( 73 , 112 ), the duration of mechanical ventilation ( 112 ) and a diagnosis of ARDS ( 73 , 74 ) have been associated with worse fibrosis on follow-up scan. Recently, shorter leukocyte telomere length, a risk factor for other fibrotic lung diseases including idiopathic pulmonary fibrosis (IPF), has been associated with post-COVID fibrotic changes on CT ( 112 ).…”
Section: Post-acute Sequelae Of Covid-19mentioning
confidence: 94%
“…Pulmonary function testing in these subjects revealed a correlation between reduced DLCO and severity of illness with women and elderly patients having a higher likelihood of having a diffusion impairment. Other studies have found that higher inflammatory markers (C-reactive protein, LDH and interleukin-6) ( 102 , 110 – 112 ), high d-dimer ( 113 ), white blood cell count ( 110 ), albumin level ( 102 ), older age ( 74 , 113 ), male sex ( 113 , 114 ), underlying co-morbidities ( 113 ), ICU admission ( 114 ), longer hospital stay ( 74 , 111 ), the need for mechanical ventilation ( 73 , 112 ), the duration of mechanical ventilation ( 112 ) and a diagnosis of ARDS ( 73 , 74 ) have been associated with worse fibrosis on follow-up scan. Recently, shorter leukocyte telomere length, a risk factor for other fibrotic lung diseases including idiopathic pulmonary fibrosis (IPF), has been associated with post-COVID fibrotic changes on CT ( 112 ).…”
Section: Post-acute Sequelae Of Covid-19mentioning
confidence: 94%
“…By the end of the treatment, the GGO and peripheral involvement were absorbed, leaving only the fibrotic lesion. Zou et al (2021) 25 studied the outcome and found improvement and sometimes the resolution of fibrosis occurs after 3 months in COVID-19 patients. In another study, however, in most patients, the pulmonary fibrosis was settled in three months 26 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Ang II plays a role in tissue fibrosis through angiotensin type 1 receptor (AT1) in cardiac, renal, pulmonary, abdominal tissues, and systemic sclerosis (Murphy et al, 2015). Pulmonary fibrosis impairs pulmonary function affecting the oxygen exchange in Covid-19 patients (Razzaque and Taguchi, 2003;Zou et al, 2021). Using pathway analysis, we demonstrate that pancreatic secretions are associated with RAS dysfunction, causing the immune system's hyperactivation and coagulation abnormalities leading to multi-organ failure.…”
Section: Role Of Upregulated Pancreatic Secretomementioning
confidence: 91%